Pengaruh Media Sosial dalam Peningkatan Kesiapsiagaan dan Respon Bencana pada Mahasiswa - Hayati, Hayati; Wirda, Wirda; Mauvizar, Erly (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2024)
This study aims to analyze the influence of social media on improving disaster preparedness and response among STIKES Muhammadiyah Aceh students. The approach used is quantitative with the cross-sectional method, where research is carried out at a specific point in time. Informants were selected using random sampling, and data were collected through a Guttman scale questionnaire that offered "Yes" or "No" answer choices. This method is expected to yield clear responses to the issues studied. Data analysis was conducted through stages of coding, cleaning, transferring data to a computer, presenting, and analyzing. The study results reveal that social media plays a significant role in disaster education among students. Five main indicators were identified: disaster knowledge and attitudes (98% of students acknowledge that social media increases their knowledge about disasters), information dissemination (98% recognize social media as the fastest source of information), early warning systems (52% feel the current system is inadequate), student participation (73% are willing to engage in open donations or disaster training), and social capital (62% obtain information through disaster-related social media groups or platforms).In conclusion, social media is a vital tool for enhancing disaster preparedness and accelerating information dissemination among students. However, improvements are still needed in early warning systems and the overall effectiveness of social media in disaster response.